FACTORS AFFFECTING ATTITUDE TOWARD USING MOBILE COMMERCE: MODIFIED THEORY OF TECHNOLOGY ACCEPTANCE MODEL (TAM) - Lila Widya Rahajeng; Zaki Baridwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The objectives of the research are to examine some factor that influence of age and gender on attitude toward using mobile commerce services by modified a model of Technology Acceptance Model (TAM) developed by Davis in 1989. This research was conducted at Economic and Business Faculty of Brawijaya University in Malang by use a sample survey methodology. Researcher has got response from 244 students of Accounting Majors who ever use mobile commerce. The data were analyzed by use Partial Least Square (PLS). The result of analysis for this model shows that the construct attitude affected by perceived usefulness and perceived ease-of-use, it is also found that construct of age did not affected by perceived usefulness and perceived ease-of-use, along with the construct gender did not affected by perceived usefulness but influenced of perceived ease-of use to use mobile commerce. This means that the attitude to use mobile commerce is influenced by the construct perceived usefulness and perceived ease-of-use, also perceived ease of use is affected by gender. The implication of the research relevant to the management and system analyst to consider factors of perceived usefulness and perceived ease-of-use in applying and developing mobile commerce transaction. Moreover, it is also important to consider factor of age and gender in affect the perceived usefulness and age factor in affect the perceived ease-of-use. Key words: Technology Acceptance Model (TAM), mobile commerce, attitude, perceived usefulness. Perceived ease of use, age, gender.